In vivo Brain Delivery of v-myc Overproduced Human Neural Stem Cells via the Intranasal Pathway: Tumor Characteristics in the Lung of a Nude Mouse. Issue 1 (1st January 2015) - Lee, Eun Seong; Im, Hyung-Jun; Kim, Han Soo; Youn, Hyewon; Lee, Hong J.; Kim, Seung U.; Hwang, Do Won; Lee, Dong Soo
We aimed to monitor the successful brain delivery of stem cells via the intranasal route and to observe the long-term consequence of the immortalized human neural stem cells in the lungs of a nude mouse model. Stably immortalized HB1.F3 human neural stem cells with firefly luciferase gene (F3-effluc) were intranasally delivered to BALB/c nude mice. Bioluminescence images were serially acquired until 41 days in vivo and at 4 hours and 41 days ex vivo after intranasal delivery. Lungs were evaluated by histopathology. After intranasal delivery of F3-effluc cells, the intense in vivo signals were detected in the nasal area, migrated toward the brain areas at 4 hours (4 of 13, 30.8%), and gradually decreased for 2 days. The brain signals were confirmed by ex vivo imaging (2 of 4, 50%). In the mice with initial lung signals (4 of 9, 44.4%), the lung signals disappeared for 5 days but reappeared 2 weeks later. The intense lung signals were confirmed to originate from the tumors in the lungs formed by F3-effluc cells by ex vivo imaging and histopathology. We propose that intranasal delivery of immortalized stem cells should be monitored for their successful delivery to the brain and their tumorigenicity longitudinally.